The association study of Apolipoprotein E polymorphisms and chronic obstructive pulmonary disease in the Chinese population: A case-control study - Zhang, Yuan (Medicine (Baltimore), 2020)
Chronic obstructive pulmonary disease (COPD) patients have increased cardiovascular morbidity and mortality. Apolipoprotein E (ApoE) is involved in chronic inflammation which is the common characteristic of emphysema and cardiovascular disease. ApoE polymorphisms are associated with cardiovascular disorders and atherosclerosis. There is no report about the association between ApoE polymorphism and COPD. A total of 480 COPD patients and 322 controls who were unrelated Chinese Han individuals were enrolled. Rs429358 and rs7412 were genotyped and the associations between ApoE polymorphisms and COPD risk were analyzed by logistic regression analysis. Online software SHEsis were applied to perform linkage disequilibrium (LD) and haplotypes analysis. The interactions of ApoE and environmental factor on COPD susceptibility was analyzed by software MDR3.0.2. No significant association was found between rs429358, rs7412 and COPD under different genetic models. Rs429358 and smoking formed the best model in the MDR analysis. The frequency of E2/E2 phenotype was the lowest in 2 groups. E3/E3 was the most common phenotype, accounting for 69.8% of COPD patients and 68.9% of controls. No statistically difference was identified between the cases and controls under different phenotypes. This was the first genetic association study between ApoE and COPD. No positive association was found in the Chinese Han population. Rs429358 and smoking status existed significant interaction, indicating that both of ApoE and smoking may be involved in the development of COPD disease.